The Expert System of Cholesterol Detection Based on Iris Using the Gabor Filter - Simangunsong, Louis Paulus Doli; Napitupulu, Indri Natalia; Lumbantoruan, Rina E; Zalukhu, Situlus; Zebua, Mariana (Sinkron : jurnal dan penelitian teknik informatika, 2019)
Abstract Cholesterol is a systemic disease. Many complications of its could affect other organs due to uncontrolled cholesterol / fat in the blood. One of them is coronary heart disease. One way to recognize someone having cholesterol is through the eyes. By using the Iridology method, cholesterol disease in a person's body can be detected or seen through the iris of the eye. Checking cholesterol-related conditions is usually done in a hospital or pharmacy. But the problem is that people are still lazy to check their cholesterol. Therefore, we need a software that can make it easier for people to do cholesterol checks. This device will detect cholesterol by using image processing techniques through the iris image accompanied by the Gabor Filter method. From 15 tested data, 13 iris image images were successfully identified, so that the percentage of success of this program was 86%.with 35 trained data.